Implementasi Metode Pembelajaran Aktif Dalam Proses Belajar Siswa Sekolah Dasar - Silvia Julianti Dewi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research is motivated by a paradigm shift from traditional teacher-centered learning to student-centered learning. This study aims to determine the impact of implementing active learning methods on student learning in elementary schools. This study used a literature review method. The results showed an increase in learning outcomes, with students learning using active learning methods showing higher learning outcomes than those learning using traditional methods. Keywords: active learning, learning achievement, elementary school